Extração de glifosato e ácido aminometilfosfônico da madeira de eucalipto e quantificação por HPLC-ICP-MS/MS - Emanuella Mesquita Pimenta (2016)
Glyphosate is a non-selective post-emergent organophosphate herbicide that can be absorbed by leaves and translocated throughout the plant. Due to its high efficiency, it is the main herbicide used in the world and therefore the target of several researches. However, scarce are the methodologies of detection of this compound in eucalyptus. Because of it, the objective of this research was to develop and validate a technique to extract the glyphosate and the aminomethylphosphonic acid (AMPA) from the eucalyptus wood and to analyze by high performance liquid chromatography coupled to the triple quadrupole mass spectrometer with inductively coupled plasma (HPLC-ICP -MS / MS). The steps of the work consisted in (i) comparing gas chromatography techniques (GC-MS and GC-NPD) and high performance liquid chromatography (HPLC-DAD and HPLC-ICP-MS / MS) in the quantification of glyphosate and AMPA; (ii) to establish the optimal conditions to analyze glyphosate and its metabolite by HPLC-ICP-MS / MS; (iii) to develop a methodology for the extraction of these compounds in samples of eucalyptus wood and (iv) to validate the optimized method by performing the statistical tests required to confirmation of the merit figures: linearity, selectivity, limit of detection and quantification, matrix effect, precision and accuracy. For the study of the chromatographic systems were evaluated parameters such as selectivity, linearity and limit of detection (LD). Linearity was confirmed for all the techniques investigated with determination coefficient (R2) higher than 0.99 in the concentration ranges studied. It was observed selectivity in all chromatographic systems evaluated, with good resolution of the chromatograms and separation of the compounds in less than 5 minutes by HPLC-ICP-MS / MS and longer analysis time (20 minutes) obtained by HPLC-DAD. In this study, the HPLC-ICP-MS / MS was considered the most adequate technique for quantification of glyphosate and AMPA. The proposed extraction method consisted of the addition of 5 mL of ultrapure water with pH = 11 in 0.5 g of sample with vortexing for 60 seconds and centrifugation for 10 minutes at 4000 rpm. The extract was concentrated and reconstituted with buffer solution of 50 mM acetic acid / ammonium acetate: 5 mM tetrabutylammonium: 1% methanol (pH = 4.7) and injected into HPLC-ICP-MS / MS. Separation of the compounds was satisfactory with total analysis time less than 5 minutes. An average recovery of 72% (DPR ± 4.08) was obtained for glyphosate and above 100% for AMPA. This high value in AMPA recovery was caused by interferents observed at the same retention time of the analyte and to remove it, two methods of cleaning the extracts were studied. The method was selective and linear for glyphosate, with a detection limit of 0.82 mg kg-1 and a quantification limit of 2.72 mg kg-1, below the maximum residue limits defined for soybean (10 mg kg -1 ) and cotton (3 mg kg-1). The method presents potential for quantification of glyphosate and AMPA in eucalyptus wood, however, it was observed low precision and accuracy, and future studies are necessary to the cleaning the extracts and minimization of the matrix effect